Driving with the Handbrake On: Competition Class Actions under the Consumer Rights Act 2015. Issue 3 (May 2016) - Higgins, Andrew
Abstract : This paper examines the new class action procedure for competition cases established by the Consumer Rights Act 2015. It examines whether the legislation and the procedural rules for the Competition Appeal Tribunal address the failures of previous procedures, focusing on three issues in particular i) the treatment of conflicting interests amongst class members ii) the rules on certifying collective proceedings; and iii) rules on funding. It argues that while the Act is a considerable improvement on what preceded it, the safeguards adopted will act as a drag on meritorious and unmeritorious claims alike, and as such there is likely to be continued under‐enforcement of competition law.